Qualitative and Quantitative Analysis of Dexamethasone in Rheumatic Pain Herbal Medicine Using Thin-Layer Chromatography (TLC) – Densitometry - Desy Ayu Irma Permatasari; Novita Kurniasri; Muladi Putra Mahardika (Universitas Muhammadiyah Yogyakarta, 2021)
Chemical medicine is chemical substances that is used as the main ingredient of chemical drugs. This compound is usually added to herbal medicine preparation to strengthen the indication of the traditional medicine.Chemical medicine was prohibited from being added to traditional medicinal preparations. But in reality, a lot of medicinal herbs could have contained medicinal chemicals on the market sale. This purpose of this research was to know the chemical contamination of the dexamethasone also the concentration contained in the rheumatic pain herbal medicine. This research was used three kind of rheumatic pain herbal medicine sample to identify dexamethasone, the sample code is S1, S2, and S3. The analysis of qualitative method are organoleptic test, FTIR characteristic test, TLC evaluation. The analysis of quantitative were purposed to know the dexamethasone concentration contained on the rheumatic pain herbal medicine using TLC-Densitometric method. The result show that the three sample of rheumathic pain herbal medicine were contaminated by dexamethasone chemical medicine. Based on organoleptic test, the results show color, smell, and taste. Characterization of the dexamethasone using FTIR were to know functional groups of dexamethasone contained in the rheumatic pain herbal medicine sample, the functional groups of the sample S1, S2, and S3 were compared to dexamethasone standard. To identify of TLC method, obtained Rf value of dexamethasone standard and the sample, visualizing a stain color purple-fluorescence on the UV 254 nm. The analysis of quantitative dexamethasone concentration using TLC-Densitometric showed the presence of dexamethasone in the sample for S1, S2 and S3. The concetration of dexamethasone obtained of sample S1, S2, S3 were 1014.64 µg/g ; 131.15 µg/g ; 135.54 µg/g respectively.